Historical evolution of the concept of health in Western medicine - Conti, Andrea Alberto (Acta Biomedica Atenei Parmensis, 2018)
“Health” is a positive multi-dimensional concept involving a variety of features, ranging from ability to integrity, from fitness to well-being. According to the first principle of the constitution of the World Health Organization “Health is a state of complete physical, mental and social well-being and not merely the absence of disease or infirmity”. This constitution was adopted by the International Health Conference held in New York in June-July 1946 and became operative in April 1948. This classical, seventy-year old definition of the World Health Organization is nowadays considered a historical one and it stands as a fundamental milestone of a diachronic track beginning, in Western medicine, with the definition of health proposed by Hippocrates and his School. For Hippocrates health was the state of equilibrium of four humours. This philosophical-naturalistic definition has been flanked in the history of Western medicine by various concepts of health and disease, alternatively based, according to different scientists and in different medical contexts and periods, on epidemiological, anatomical, physiological, functional, social and molecular perspectives. Since biomedical definitions are always prone to integration and updating, depending on the continuous achievements of medical science and bioethics, the fascinating journey through the concepts of health and disease, the fundamental milestones of which are here briefly proposed, is still in progress.